Five Efforts in Building the Character of Students - Rahawarin, Yunus; Taufan, Muhammad; Oktavia, Gifa; Febriani, Afifah; Hamdi, Hafizul; Iskandar, M. Yakub (Al-kayyis: Journal of Islamic Education, 2023)
Teachers' efforts to develop students' morals are an integral aspect of the character education process. This research aims to find out how moral belief teachers work in the classroom, outside the classroom, obstacles and how to overcome the development of student morals. This research uses a qualitative method with a case study approach. The data source was taken from five informants through in-depth interviews who were selected using purposive sampling techniques, one informant was a teacher who taught Aqidah Akhlak. All interview results were then analyzed thematically by Miles and Huberman. The results of the analysis found that efforts to develop morals in students to become role models; give advice; speak politely; participate in school activities and provide sanctions. The results of this research can become the basis for developing moral development programs in educational institutions so that the educational process not only includes the transfer of knowledge but also the formation of individuals with noble morals.